2017
DOI: 10.1007/978-3-319-66700-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Computing Constrained Approximate Equilibria in Polymatrix Games

Abstract: This paper is about computing constrained approximate Nash equilibria in polymatrix games, which are succinctly represented manyplayer games defined by an interaction graph between the players. In a recent breakthrough, Rubinstein showed that there exists a small constant ǫ, such that it is PPAD-complete to find an (unconstrained) ǫ-Nash equilibrium of a polymatrix game. In the first part of the paper, we show that is NP-hard to decide if a polymatrix game has a constrained approximate equilibrium for 9 natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…On the positive side, Cai and Daskalakis [2], proved that NE can be efficiently found in polymatrix games where every 2-player game is zero-sum. Ortiz and Irfan [13] and Deligkas, Fearnley, and Savani [7] produced QPTASs for polymatrix games of bounded treewidth (in addition to the FPTAS of [13] for tree polymatrix games mentioned above). For general polymatrix games, the only positive result to date is a polynomial-time algorithm to compute a ( 1 2 + δ)-NE [8].…”
Section: Related Workmentioning
confidence: 99%
“…On the positive side, Cai and Daskalakis [2], proved that NE can be efficiently found in polymatrix games where every 2-player game is zero-sum. Ortiz and Irfan [13] and Deligkas, Fearnley, and Savani [7] produced QPTASs for polymatrix games of bounded treewidth (in addition to the FPTAS of [13] for tree polymatrix games mentioned above). For general polymatrix games, the only positive result to date is a polynomial-time algorithm to compute a ( 1 2 + δ)-NE [8].…”
Section: Related Workmentioning
confidence: 99%
“…Constrained Nash equilibria attracted the attention of many authors, who proved NP-completeness for two-player games [23,14,6] and ETR-completeness for three-player games [6,7,8,9,22] for constrained exact Nash equilibria. Constrained approximate equilibria have been studied, but so far only lower bounds have been derived [2,25,11,19,18]. It has been observed that sampling methods can give QPTASs for finding constrained approximate Nash equilibria for certain constraints in two player games [19].…”
Section: Applicationsmentioning
confidence: 99%
“…Subsequently, it was used to produce algorithms for finding approximate equilibria in normal form games with many players [3], sparse bimatrix games [4], tree polymatrix [5], and Lipschitz games [20]. It has also been used to find constrained approximate equilibria in polymatrix games with bounded treewidth [18].…”
Section: Introductionmentioning
confidence: 99%
“…In our results, we check 201 different points for α in each iteration. For a justification of the reasonableness of this choice, see Appendix A in the full version of this paper [21].…”
Section: Algorithmsmentioning
confidence: 99%
“…The underlying reason is that the number of players in the polymatrix game (i.e., number of types) affects the running time much more that the number of actions (i.e., number of items/troops). Also see Appendix B in the full version of this paper[21].…”
mentioning
confidence: 99%